The Postnatal Growth and Retinopathy of Prematurity Model: A Multi-institutional Validation Study. (4th May 2022) - Ahmed, Islam S. H.; Aclimandos, Wagih; Azad, Nadia; Zaheer, Naima; Barry, John Sebastian; Ambulkar, Hemant; Badeeb, Adham; Osman, Ihab Mohamed; Rashad, Shaheera; Helaly, Hany Ahmed
ABSTRACT: Purpose: The G-ROP model was proposed to improve the retinopathy of prematurity (ROP) screening efficiency. It is based on gestational age, birth weight and postnatal weight gain. The current study aimed to validate the G-ROP model's ability to predict ROP in cohorts of premature infants from Egypt and the United Kingdom (UK). Methods: We retrospectively reviewed the records of preterm infants born between 1st of January and 30th of June 2018 with a known outcome for ROP screening and regular weight measurements until day 39 after birth. We applied the G-ROP model to the study group and calculated the sensitivity of the model for detecting Early Treatment of ROP (ETROP) study type 1 ROP and for any ROP and calculated the reduction of the number of infants requiring ROP screening by the model application. Results: We applied the G-ROP model on 605 infants (504 from Egypt and 101 from the UK). The model successfully predicted all type 1 ROP cases (100% sensitivity) in both cohorts (95% confidence interval [CI], 91.1–100% in the Egyptian cohort and 65.5–100% in the UK cohort). The model reduced the number of infants requiring screening by 14.1% in the Egyptian cohort and 21.8% in the UK cohort. Conclusions: The G-ROP model was successfully validated for detecting type 1 ROP and in both cohorts from Egypt and the UK.